My teacher, my friend - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
Numerous studies have been carried out to examine the impact of out-of-class faculty interaction with students on student satisfaction and success in higher education. One such study was recently carried out by Ibtesan Halawah at Ajman University in Abu Dhabi, U.A.E. Her report entitled'The Impact Of Student-Faculty Informal Interpersonal Relationships On Intellectual And Personal Development'was published in the College Student Journal, Sep 2006, Vol 40, Issue 3.